Links between patterns of racial socialization and discrimination experiences and psychological adjustment: A cluster analysis. Issue 7 (12th August 2014) - Ajayi, Alex A.; Syed, Moin
ABSTRACT: This study used a person‐oriented analytic approach to identify meaningful patterns of barriers‐focused racial socialization and perceived racial discrimination experiences in a sample of 295 late adolescents. Using cluster analysis, three distinct groups were identified: Low Barrier Socialization‐Low Discrimination, High Barrier Socialization‐Low Discrimination, and High Barrier Socialization‐High Discrimination clusters. These groups were substantively unique in terms of the frequency of racial socialization messages about bias preparation and out‐group mistrust its members received and their actual perceived discrimination experiences. Further, individuals in the High Barrier Socialization‐High Discrimination cluster reported significantly higher depressive symptoms than those in the Low Barrier Socialization‐Low Discrimination and High Barrier Socialization‐Low Discrimination clusters. However, no differences in adjustment were observed between the Low Barrier Socialization‐Low Discrimination and High Barrier Socialization‐Low Discrimination clusters. Overall, the findings highlight important individual differences in how young people of color experience their race and how these differences have significant implications on psychological adjustment.